Regulação das guanosina trifosfatases RHO na redução da migração de células intestinais induzida por cepas selvagem e padrão de Escherichia coli enteropatogênica - Cavalcante, Paloma Araújo (2013)
Enteropathogenic Escherichia coli (EPEC) is an important pathogen associated with diarrheal diseases. Intestinal infections cause impairment of the intestinal barrier and one of the earliest response mechanisms to recover is migration of the intestinal cells to cover the injured area. The key proteins that regulate cell migration are small Rho GTPases, Rac1, Cdc42 and RhoA. The alanyl-glutamine (Ala-Gln) increases this migration process, however the mechanisms involved in this response are still unknown. Thus, we investigated the effect of a wild type strain and standard (E2348/69) of EPEC strain and a commensal E. coli HS on intestinal cell migration, as well as transcriptional regulation and gene expression of Rho GTPases and the role of supplemental Ala-Gln in the migration process in the presence or absence of infection. Infection by EPEC strains and commensal E. coli HS significantly reduced intestinal cell migration. However, this effect was more pronounced in cells infected by the strains of EPEC compared to those infected by the commensal strain of E. coli HS. We observed a high percentage of necrotic cells, about 30%, induced only by EPEC strain pattern 12 and 24 hours after infection. The addition of Ala-Gln in uninfected cells significantly stimulated in a dose dependent migration after 24 hours. However, when this nutrient was added over 12 and 24 hours in the presence of infection, there was no reversion of the damage. Regarding the gene expression of Rho GTPases, we observed an increase in transcription of rac1 in cells that had been infected by the strains of EPEC and E. coli HS as well as an increase in rhoA transcription in cells infected with EPEC strain pattern at 2 hours after infection. However, the analysis of proteins by immunofluorescence, RhoA and Cdc42 shown to be elevated in cells infected with EPEC pattern when compared to the control. Whereas cells infected with wild EPEC strain was observed an increase of Rac1 and reduction of RhoA. These data showed that cell migration is reduced mainly by the intestinal pathogenic strains of EPEC, in regulating gene transcription and expression of the protein Rho GTPases. Supplementation with Ala-Gln in intestinal cells only promoted cell migration in the absence of infection.